PEMANFAATAN ORGAN TUBUH MANUSIA MELALUI WASIAT BERDASARKAN HUKUM ISLAM - INGRID INGKA PRAMESWARI (PREMISE LAW JURNAL, 2015)
The progress of science and technology in the health field to cure one of the body organs has damage then someone able to perform organ transplants obtained from living donor and deceased donor. The existence of high sense of humanity to help other people who need organ became the basic of a person to make a will to give their organs. The result of this study showed that the position of law of wills according to Islamic law viewed from the condition of donors after his/her death for the goods of other people who need it is mubah (permissible). The utilization of human body organ through a will according to Islamic law because the benefit it brings is bigger than the disbenefit exists, namely to help other people who need the organ through organ transplant. The will is made voluntary, without any compulsion, and must be agreement from the family. Keywords: Human Body Organ, Will, Islamic Law